Quantitative methods for the social sciences : a practical introduction with examples in SPSS and stata - Stockemer, Daniel (Cham : Springer, 2019)
This textbook offers an essential introduction to survey research and quantitative methods. Building on the premise that statistical methods need to be learned in a practical fashion, the book guides students through the various steps of the survey research process and helps to apply those steps toward a real example. In detail, the textbook introduces students to the four pillars of survey research and quantitative analysis: (1) the importance of survey research, (2) preparing a survey, (3) conducting a survey and (4) analyzing a survey. Students are shown how to create their own questionnaire based on some theoretically derived hypotheses to achieve empirical findings for a solid dataset. Lastly, they use said data to test their hypotheses in a bivariate and multivariate realm. The book explains the theory, rationale and mathematical foundations of these tests. In addition, it provides clear instructions on how to conduct the tests in SPSS and Stata. Given the breadth of its coverage, the textbook is suitable for introductory statistics, survey research or quantitative methods classes in the social sciences.
Introduction -- The Nuts and Bolts of Empirical Social Science -- A Short Introduction to Survey Research -- Constructing a Survey -- Conducting a Survey -- Univariate Statistics -- Bivariate Statistics with Categorical Variables -- Bivariate Relationships Featuring Two Continuous Variables -- Multivariate Regression Analysis -- .
Includes bibliographical references and index.
Description based on publisher-supplied MARC data.
Keywords: Social sciences -- Research methodology; Social sciences -- Methodology